Nephrolithiasis of cows: diagnostics of slaughter animals - Kanivets , N. S. (Scientific Progress & Innovations, 2019)
The purpose of the article is to highlight data on bovine nephrolithiasis disease in Poltava region, taking into account the available information on spreading of this pathology. Research methods. In the process of work we conducted veterinary-sanitary expert examination of the internal organs (kidneys) of cattle at slaughtering, organoleptically detected nephroliths and determined their parameters. Research results. The results of the conducted veterinary-sanitary expert examination revealed stones in the kidneys in five animals, which was about 2.1 % of the total number of slaughtered animals. Uroliths were localized, mainly in the ureter, and less frequently in the calix renalis. Kidney stones were of different sizes from 1 to 14 mm, in some cases, very small stones in the form of sand grains, the so-called renal sand. At the same time, uroliths differed in shape. The some stones were large and solid, others were small and sandy. Externally, they had a smooth or rough (thorny) surface. The color varied from light gray to yellow-gray. The weight of uroliths varied from 2.1 mg (the smallest stones) to 0.98 g (the largest stones). Not rarely, during examining the kidneys, isolated cysts of different sizes were detected, which were filled with light-serous fluid. The analysis of calculus showed its mixed composition (calcium oxalate, magnesium phosphate, calcium phosphate and ammonium urate), which is similar to the results of other researchers and it is coordinated with the hypothesis of the diversity of uroliths’ composition in cattle. The elements of scientific novelty. Small stones (sand) are found in the calix renalis of cows. Practical significance. Clarifying the role of ecological and alimentary factors in the development of kidney stones in cows deserves attention.